ANALISIS PENGARUH BIAYA BUNGA PINJAMAN TERHADAP LABA BERSIH PERIODE SEBELUM KR ISIS DAN SELAMA KRISIS PADA PERUSAHAAN REAL ESTATE DAN PROPERTY - Hernawati Pramesti; Endang Satyawati (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2007)
This research conducted to look for the empirical evidence the influence of interest expenses of loan to net profit of company of Real Estate and Property period before and during crisis, and look for there is do not it difference of influence of interest expenses of loan to net profit of company of Real Estate and Property period before and during crisis. Hypothesis to be tested by interest expenses of loan have an effect on to net profit of company of Real Estate and Property period before and during crisis and there are difference of influence of interest expenses of loan to net profit of company of Real Estate and Property period before and during crisis. Hypothesis examination in this research use the simple linear regression to see there is or not it independent variable influence to variable dependent and use the test Chow to see this and do not it difference independent variable influence to variable dependent. Result of test of correlation of Pearson Correlations concluded that interest expenses of loan have an effect on positively to net profit of company of Real Estate and Property period before and during crisis. But result test the Chow show no difference of influence of interest expenses of loan to profit of company of Real Estate and Property period before and during crisis. Pursuant to above mentioned analysis result hence suggested to give the boundaries data so that not happened the too high data fluctuation. Need the existence of research searching empirical evidence about how big difference of influence of interest expenses of loan to net profit of company of Real Estate and Property period before and during crisis. Become not only searching this or not it difference but searched how big that difference happened. Keyword: Interest Expenses of Loan, Net Profit and Crisis